Comparison of immunogenicity and persistence between inactivated hepatitis A vaccine Vealive® and Havrix® among children: A 5-year follow-up study. Issue 10 (2nd October 2016) - Yu, Chengkai; Song, Yufei; Qi, Yangyang; Li, Chanjuan; Jiang, Zhiwei; Li, Chen; Zhang, Wei; Wang, Ling; Xia, Jielai
ABSTRACT: Background: Inactivated vaccines for hepatitis A virus (HAV) infection are widely used in China. Mass vaccination programs drive the need for data on long-term persistence of vaccine-induced protection.Methods: A prospective, randomized, open-label clinical trial was conducted to compare geometric mean concentrations (GMCs) and seroconversion rates (SRs) of anti-HAV antibody elicited by the inactivated vaccines Healive and Havrix for 5 y post immunization, in which 400 healthy children were randomly assigned in a 3:1 ratio to receive 2 doses of Healive or Havrix at 0 and 6 month. Anti-HAV antibody concentration was detected by microparticle enzyme immunoassay (MEIA) during the study. Furthermore, an attempt was made to predict persistence of protective immunogenicity by using a suitable statistical model.Results: The GMCs were significantly higher after vaccination with Healive than after Havrix as comparator vaccine at 1, 6, 7, 18, 30, 42, 54 and 66 month ( P < 0.01) with the peak point at 7 month (3427.2 mIU/ml for Healive and 1441.9 mIU/ml for Comparator). Similarly significant differences of SRs were found between the 2 groups at 1 and 6 month ( P < 0.01). Afterwards, the SRs of both groups reached 100% at 7 month and did not decline until 66 month(99.1% for Healive and 97.5% for Comparator). A linear mixed model with a change point at 18 month(Model 3) was found to be suitable to predict persistence of protective immunogenicity induced by vaccines. It was estimated that the duration of protection for Healive was at least 20 y with a lower limit of GMC 95% confidence interval (CI) no less than 20 mIU/mL.Conclusions: Compared with Havrix, the new preservative-free inactivated hepatitis A vaccine (Healive) in 2 doses showed better persistence of antibody concentrations for 5 y after full-course immunization among children and the persistence of protective immunogenicity was estimated for at least 20 y.